APPLICATION OF THE TOTAL PHYSICAL RESPONSE METHOD IN ARABIC LEARNING TO IMPROVE UNDERSTANDING IN CHILDREN EARLY - Samsul Fajeri; Husin; Anggun muthoharoh; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Arabic is a foreign language which is quite difficult to understand for children who are just learning another language, besides their mother tongue. There are many obstacles encountered by educators in the introduction of Arabic to children. It is very important for the teacher to choose the right method to make learning more fun and easy to understand. Therefore in this study the researcher has the goal of increasing children's understanding of learning Arabic using the Total Physical Response method. This research was conducted at MIN 14 Hulu Sungai Tengah. This study uses a qualitative descriptive field research method. The results of this study indicate that the TPR method: easy to understand and apply, does not require more power, does not require additional fees, contains elements of game movement so that it can relieve stress on children, learning time becomes more efficient, communication between teachers and children becomes more effective the child becomes more expressive